FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL PEMODERASI - Vivi Adeyani Tandean; Piter Nainggolan (Jurnal Akuntansi Bisnis, 2017)
Taxation is an important issue to sustain a country’s revenue. The main obstacle in the context of state income tax in this sector is tax avoidance. Minimizing of tax burden can be influenced by executive’s character, company’s size, profitability and institutional ownership.This study aims to examine the factors that affect tax avoidance. This study uses 120 manufacturing companies. Sample methods in this study is judgment sampling. This study’s hypothesis is tested with classical assumptions and multiple regression analysis and residual regression analysis using SPSS version 20 software. Conclusions for this research is executive’s character does not have sufficient evidence to have impact on tax avoidance. Company’s size and profitability have sufficient impact on tax avoidance. Institutional ownership variable can be able to moderate various factor which have impact on tax avoidance.Keywords : tax avoidance